A powerful meta-heuristic search algorithm for solving global optimization and real-world solar photovoltaic parameter estimation problems. (May 2022) - Duman, Serhat; Kahraman, Hamdi Tolga; Sonmez, Yusuf; Guvenc, Ugur; Kati, Mehmet; Aras, Sefa
Abstract: The teaching-learning-based artificial bee colony (TLABC) is a new hybrid swarm-based metaheuristic search algorithm. It combines the exploitation of the teaching learning-based optimization (TLBO) with the exploration of the artificial bee colony (ABC). With the hybridization of these two nature-inspired swarm intelligence algorithms, a robust method has been proposed to solve global optimization problems. However, as with swarm-based algorithms, with the TLABC method, it is a great challenge to effectively simulate the selection process. Fitness-distance balance (FDB) is a powerful recently developed method to effectively imitate the selection process in nature. In this study, the three search phases of the TLABC algorithm were redesigned using the FDB method. In this way, the FDB-TLABC algorithm, which imitates nature more effectively and has a robust search performance, was developed. To investigate the exploitation, exploration, and balanced search capabilities of the proposed algorithm, it was tested on standard and complex benchmark suites (Classic, IEEE CEC 2014, IEEE CEC 2017, and IEEE CEC 2020). In order to verify the performance of the proposed FDB-TLABC for global optimization problems and in the photovoltaic parameter estimation problem (a constrained real-world engineering problem) a very comprehensive and qualified experimental study was carried out according to IEEE CEC standards. Statistical analysis results confirmed that the proposed FDB-TLABC provided the best optimum solution and yielded a superior performance compared to other optimization methods. Highlights: A powerful meta-heuristic search algorithm called FDB-TLABC was developed. The proposed FDB-TLABC algorithm in this study is presented as potentially one of the most powerful MHS algorithms in the literature. The proposed algorithm is used for solving Solar PV parameter estimation, which is an important real-world problem in the field of renewable energy. The superiority of the proposed algorithm over its competitors was made between the obtained optimization results in the literature.